2023
DOI: 10.3390/polym15143043
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Printing Parameters to Enhance Tensile Properties of ABS and Nylon Produced by Fused Filament Fabrication

Abstract: This study aimed to identify the optimum printing parameters for the fused filament fabrication (FFF) of acrylonitrile butadiene styrene (ABS) and polyamide (nylon), to improve strength properties. For this purpose, the methodology of the paper involves an experimental study that used Taguchi’s method to identify the effects of the infill pattern, infill density, and printing speed on the mechanical properties of the materials. ABS and nylon plastic parts were tested in tension to failure. Based on the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Based on the review of the scientific literature [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], it can be concluded that the mechanical properties of FDM 3D-printed ABS polymer materials have been explored from various perspectives, such as the impacts of the raster angle [31][32][33][34], layer thickness [35][36][37], infill percentage [38][39][40][41], printing speed [42][43][44], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the review of the scientific literature [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], it can be concluded that the mechanical properties of FDM 3D-printed ABS polymer materials have been explored from various perspectives, such as the impacts of the raster angle [31][32][33][34], layer thickness [35][36][37], infill percentage [38][39][40][41], printing speed [42][43][44], etc.…”
Section: Introductionmentioning
confidence: 99%